RESULTS OF PHARMACOEPIDEMIOLOGIC STUDY OF ARTERIAL HYPERTENSION PIFAGOR IV: PHYSICIANS COMPLIANCE - M. V. Leonova; L. L. Steinberg; Yu. B. Belousov; D. V. Belyavskaya; O. I. Vydrina; E. Yu. Pasternak; D. Yu. Belousov (Российский кардиологический журнал, 2015)
Aim. To conduct the new stage of pharmaco-epidemiologic study of AH — PIFAGOR IV to study the structure and prevalence of various classes of antihypertensive drugs usage (ADU) in clinical practice. Material and methods. The study was conducted with physicians questionnaires usage (GPs, cardiologists), having the practice of AH patients treatment with specially developed questionnaires. Totally 1105 physicians studied (67,5% GPs, 28,1% cardiologists, 8,2% the others) from 73 cities and other places during the period from february to july 2013. Results. The ADU structure by physicians in AH patients includes 5 main recommended drug classes: ACE inhibitors (24,2%), b-adrenoblockers (18,9%), diuretics (18,9%), calcium channel antagonists (17,4%) and angiotensin II receptor blockers (16%), totally 95,4%. Other classes included: central-acting drugs — 3,4%, a-adrenoblockers — 1,2%. In ACE inhibitors class the main are five following: perindopril (20,3%), enalapril (18,3%), lisinopril (18,5%), ramipril (14,2%) and fosinopril (13,6%). In b-blocker class the main are bisoprolol (30,2%), metoprolol in modified and common compounds (25,2%), carvedilol (16%). Diuretic class consists by a half of indapamide (54,8%), torasemide (18,4%), hydrochlorothiazide (19,4%). In calicum antagonists the main are amlodipine (32,6%) including S-amlodipine (1,8%), nifedipine in various forms (21,5%), with modified release — 14,3%, verapamil in various forms (14,6%), diltiazem (13%). In ARBII the main are losartan (37,3%), valsartan (29,9%). Central drug class included moxonidine (74,1%), rilmenidine (8%), clopheline (18%). The part of physicians compliant to fixed drug combinations increased to 52,6%; the part of ACE inhibitors with calcium channel blockers increased to 29,1%, and decrease found for b-blockers with diuretic — 15,6%. Physicians use more adequate criteria for AHT and recommended criteria for treatment effectiveness control (target BP).Conclusion. Analysis of physicians compliance showed the relevance to national guidelines for diagnostics and treatment of AH; physicians actively use combination therapy and modern fixed dose compounds.